Sweet and sticky: increased cell adhesion through click-mediated functionalization of regenerative liver progenitor cells - Amaziah R. Alipio; Melissa R. Vieira; Tamara Haefeli; Lisa Hoelting; Olivier Frey; Alicia J. El Haj; Maria C. Arno (Communications Biology)
Abstract The burgeoning field of cell therapies is rapidly expanding, offering the promise to tackle complex and unsolved healthcare problems. One prominent example is represented by CAR T-cells, which have been introduced into the clinic for treating a variety of cancers. Promising cell therapeutics have also been developed to promote tissue regeneration, showing high potencies for the treatment of damaged liver. Nevertheless, in the remit of regenerative medicine, cell-therapy efficacies remain suboptimal as a consequence of the low engraftment of injected cells to the existing surrounding tissue. Herein, we present a facile approach to enhance the adhesion and engraftment of therapeutic hepatic progenitor cells (HPCs) through specific and homogeneous cell surface modification with exogenous polysaccharides, without requiring genetic modification. Coated HPCs exhibit significantly increased markers of adhesion and cell spreading and demonstrate preferential interactions with certain extra-cellular matrix proteins. Moreover, they display enhanced binding to endothelial cells and 3D liver microtissues. This translatable methodology shows promise for improving therapeutic cell engraftment, offering a potential alternative to liver transplantation in end-stage liver disease.